Mergers and aquisitions in India:motives,barriers and outcomes - Shah, Siddharth (2012)
This paper examines the various factors that need to be accounted for while analysing a company undertaking a merger or an acquisition. From the motives behind the decisions to enter into a Merger or Acquisition to the barriers it faces during the process to the immediate as well as future outcomes have been projected in this research.